A scheme for fast exploratory simulation of azimuthal asymmetries in Drell-Yan experiments at intermediate energies. The DY_AB Monte Carlo event generator - Bianconi, Andrea (arXiv.org, 2008)
In this note I report and discuss the physical scheme and the main approximations used by the event generator code DY_AB. This Monte Carlo code is aimed at preliminary simulation, during the stage of apparatus planning, of Drell-Yan events characterized by azimuthal asymmetries, in experiments with moderate center of mass energy \(\sqrt{s}\) \(<<\) 100 GeV.